Une souris verte... Organismes transgéniques, spéculations humanimales et autres bricolages du vivant - Jaclin, David (Anthropologica, 2020)
In this article, I explore the (often invisible, sometimes forgotten, and yet decisive) existence of a booming animal fellowship, that of transgenic cancerous mice. On a weekly basis, thousands of young mice “depart” from the American Charles River Breeding Laboratories, their genomes modified to guarantee future tumours. Ordered online, delivered worldwide, often transported via UPS or Purolator to an increasing number of biomedical research units, these experimental animals are simultaneously alive and already dead. Programmed to die, their genotypic profile is the result of tight immuno-oncological manipulations. Reflecting on the the vital qualities of these mice (i.e., nutrition, reproduction, expression), I propose a series of reflections that are no longer solely focused on identity (human, animal, hybrid), but also on the capacities (recombined, trans-specific, emergent) exhibited by those living beings experimenting at once novel and standardised modalities of existence. I thus problematize several of the registers driving our modernity (boundaries of specified affiliations, circulation of affective qualities beyond individualised bodies, and surges of anthropocenic crystalizations). In doing so, I examine: (1) the forking of other-than-human intelligences and their commodification; (2) the ontological and epistemological qualities of an animality that is both other and the same; (3) the emergence of new ecological configurations in which these post-natural existences are becoming programmable at the same time as incommensurable, interchangeable and particular, standardised yet fostering overflowing potentialities...